2022
DOI: 10.3389/fonc.2021.789248
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Metabolomics for Prognosis of Oral Squamous Cell Carcinoma

Abstract: This study aimed to identify salivary metabolomic biomarkers for predicting the prognosis of oral squamous cell carcinoma (OSCC) based on comprehensive metabolomic analyses. Quantified metabolomics data of unstimulated saliva samples collected from patients with OSCC (n = 72) were randomly divided into the training (n = 35) and validation groups (n = 37). The training data were used to develop a Cox proportional hazards regression model for identifying significant metabolites as prognostic factors for overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Hu et al analyzed the role of salivary biomarkers in the detection of oral cancer [ 47 ]. As well, other authors have shown that saliva contains a collection of analytes, such as proteins, DNA, and mRNA, as well as several metabolites that can be potential biomarkers for clinical and translational applications [ 48 ]. Therefore, salivary analysis is an effective option for prevention, monitoring, diagnosis, and prognosis and this biological liquid could even become the first choice for the screening and identification of biomarkers given the constant contact with cancer cells inside the oral cavity [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hu et al analyzed the role of salivary biomarkers in the detection of oral cancer [ 47 ]. As well, other authors have shown that saliva contains a collection of analytes, such as proteins, DNA, and mRNA, as well as several metabolites that can be potential biomarkers for clinical and translational applications [ 48 ]. Therefore, salivary analysis is an effective option for prevention, monitoring, diagnosis, and prognosis and this biological liquid could even become the first choice for the screening and identification of biomarkers given the constant contact with cancer cells inside the oral cavity [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…To overcome the problem of increasing the wide involvement of cytokines in inflammatory conditions, it could be important to have a combination of proteomic data, including oral cytokines and salivary miRNAs, for an accurate and early diagnosis. In addition to these biomarkers, small molecules, such as non-coding RNA [ 70 ] and metabolite analysis [ 48 ], could represent a second group to build the construction of a salivary biomarker panel for OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the seven uniquely increased metabolites have been verified to possibly promote the progression of other tumors; for example, L-proline addition and L-tryptophan metabolism promote tumor invasion and metastasis and accelerate cancer progression [ 35 , 36 ]. The concentrations of 5-hydroxylysine and 3-methylhistidine have been identified as significant prognostic factors for overall survival in oral squamous cell carcinoma [ 37 ]. We speculated that these metabolites might promote the lymph node metastasis of PTC.…”
Section: Discussionmentioning
confidence: 99%
“… 32 , 33 Biomarkers for oral cancer and cancers in the organs far from the oral cavity, such as breast cancer and pancreatic cancers, have been reported. 34 , 35 , 36 , 37 To enhance the discriminability of multiple biomarkers, ML is a cornerstone. 38 , 39 Using urinary polyamine profiles, we previously used an alternative decision tree (ADTree)–based prediction method to detect CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomic biomarkers in saliva samples have been shown to represent a potential medium for cancer detection 32,33 . Biomarkers for oral cancer and cancers in the organs far from the oral cavity, such as breast cancer and pancreatic cancers, have been reported 34–37 . To enhance the discriminability of multiple biomarkers, ML is a cornerstone 38,39 .…”
Section: Introductionmentioning
confidence: 99%